The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/apa.15826
|View full text |Cite
|
Sign up to set email alerts
|

Early closure mechanisms of the ductus arteriosus in immature infants

Abstract: Aim According to experimental studies, cardiopulmonary distress decreases after closure of patent ductus arteriosus. However, early closure of the ductus using ibuprofen or indomethacin has failed to increase survival without serious morbidity. We review relevant data aiming to define optimal early management strategies that promote early closure of ductus arteriosus without serious adverse effects. Methods Literature in English was searched selectively focusing on the potential of using acetaminophen for earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 101 publications
(192 reference statements)
0
4
0
Order By: Relevance
“…Bowel perforations have been particularly associated with ibuprofen. NSAIDs also potentially complicate the PDA closure, as they prevent adherence-promoting thrombosis within the intima of the constricted PDA ( 100 ).…”
Section: Management Of Transitional Circulationmentioning
confidence: 99%
“…Bowel perforations have been particularly associated with ibuprofen. NSAIDs also potentially complicate the PDA closure, as they prevent adherence-promoting thrombosis within the intima of the constricted PDA ( 100 ).…”
Section: Management Of Transitional Circulationmentioning
confidence: 99%
“…In foetal rodents and rabbits, Heymann and Rudolph was demonstrated that prostaglandin synthesis inhibition resulted in PDA constriction 4 . As and performed observational studies using indomethacin and aspirin on human preterm infant manifesting clinical signs of a PDA 5 . However, pharmacologic closure of the PDA using indomethacin was fraught by adverse renal toxicity and lack of an intravenous preparation initially limited its use.…”
mentioning
confidence: 99%
“…Hallman et al reviewed the evolution of pharmacologic closure of the PDA with indomethacin, various formulations of Ibuprofen and more recently Paracetamol (acetaminophen) 5 that was initially described by Hammerman and coworkers 6 . Differences in preparations, route of dosing frequency and timing of administration after recognition of a haemodynamically significant PDA in very premature infants using various study designs were inconsistent in finding beneficial effects when meta‐analyses of combined studies were reported 7,8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation